Book review: Undercover: the true story of Britain’s secret police - Newburn, Tim (2013)
"Undercover: The True Story of Britain’s Secret Police." Rob Evans and Paul Lewis. Faber and Faber. June 2013. --- Undercover, written by Guardian journalists Rob Evans and Paul Lewis, aims to reveal the truth about secret police operations – the emotional turmoil, the psychological challenges and the human cost of a lifetime of deception – and asks whether such tactics can ever be justified. An important account of police cover-ups, finds Tim Newburn, with heavy implications for public trust in the police